Strategi untuk Mengurangi Turnover Intention yang dipengaruhi oleh Work Discipline, Job Demands, dan Financial Compensation - Nugroho, Novianto Eko (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2025)
This study aims to analyze the impact of work discipline, job demands, and financial compensation on employee turnover intention in the billing division of CV “X”. The research uses a quantitative descriptive analysis method with a saturated sampling technique, involving 52 employees as the sample. Data was collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS 28. The results indicate that work discipline and financial compensation have a significant positive impact on turnover intention, while job demands have a negative effect on turnover intention. This study concludes that the company should improve work discipline and financial compensation while managing job demands to reduce employees' turnover intention. The implications of this study highlight the importance of managerial policies that balance job demands, work discipline, and compensation to reduce turnover rates within the company.